Book Review - American Higher Education: A History - K. B. Melear (Arizona State University, 2011)
American Higher Education: A History, by Christopher J. Lucas is a historical narrative of the origins and development of the system of higher learning in place in contemporary America. It extends and updates earlier works in this area, and provides, as the author had hoped, "a more 'accessible' historical account, useful chiefly for nonspecialists and a more general readership . . ." but is nonetheless a thorough review of the historical underpinnings of American higher education. This work is recommended for students and professionals who seek a broad understanding of contemporary higher education and how it came to pass.